Analysis and Classification of Molecules Based on Symmetry - Popalzai, Raihana (Journal of Natural Sciences – Kabul University, 2021)
In this paper, we refine the concept of ‘shape’ into a precise definition of ‘symmetry’ and demonstrate how symmetry can be discussed systematically. We show how to classify any molecule according to its symmetry and how to use this classification to analyze molecular properties. The systematic study of symmetry is known as group theory. In most cases, group theory provides a simple, direct method for arriving at useful conclusions with minimal calculations, which is the focus of this paper. However, in some cases, it leads to unexpected results. In this article, valid foreign sources have been referenced.